The Position Of Islam In Foreign Policy During President Joko Widodo's Government (2014-2019) - Erianto Erianto (ILMU POLITIK UNIVERSITAS ISLAM NEGERI (UIN) ALAUDDIN MAKASSAR, 2019)
Indonesia is the 4th most largest population in the world, 87% of 260 million people in Indonesia is a Muslim. Indonesia is the country with the largest Muslim religion in the world, but Indonesia is not a Islamic State. Domestic political conditions influence on foreign policy. Indirectly, what happens in the country influences foreign policy issued. The author use a qualitative methodology to analyze the issue. So, the result of this research is to show the extent to which Islam influenced Indonesia's foreign policy,especially during the President Jokowi government. About how the style of President Jokowi's government in responding to domestic issues that attacked the government. This study also discusses how interest groups bring their interests to influence a policy that is produced.